2020
DOI: 10.3390/ijerph17134854
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Therapeutic Potential of Mouse Oral Mucosa Stem Cells in a Wound-Healing Diabetic Mice Model

Abstract: Diabetic wounds’ delayed healing response is still considered a major therapeutic challenge. Stem cells and derived cellular products have been an active field of research for novel therapies referred to as regenerative medicine. It has recently been shown that human oral mucosa stem cells (hOMSCs) are a readily accessible source for obtaining large quantities of stem cells. This study evaluates the potential of mouse oral mucosa stem cells (mOMSCs) to enhance wound healing in a diabetic (db/db) mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“… 34 , 35 OMSCs have been reported to be a potential solution to tackle wound healing impairment. 36 Cellular senescence is a physiological mechanism whereby a proliferating cell undergoes a stable cell cycle arrest upon damage or stress and elicits SASP, which includes pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-6, etc. 37 , 38 Herein, we found that sunitinib induced cellular senescence in OMSCs, which not only interfered with their immunomodulatory function but also resulted in the secretion of pro-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 OMSCs have been reported to be a potential solution to tackle wound healing impairment. 36 Cellular senescence is a physiological mechanism whereby a proliferating cell undergoes a stable cell cycle arrest upon damage or stress and elicits SASP, which includes pro-inflammatory cytokines such as TNF-α, IFN-γ, IL-6, etc. 37 , 38 Herein, we found that sunitinib induced cellular senescence in OMSCs, which not only interfered with their immunomodulatory function but also resulted in the secretion of pro-inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…SCs from human exfoliated deciduous teeth and oral mucosa were shown to improve skin wound healing in mice when injected around the wound or topically applied onto the wound bed highlighting the plasticity of different SC types that could be used to regenerate skin ( Nishino et al, 2011 ; Kuperman et al, 2020 ). Other studies have explored the potential of oral mucosal engineered cell sheets to apply on skin excisional and burn wounds.…”
Section: Exporting the Properties Of Oral Epithelia – The Source For Future Therapies In Wound Repair?mentioning
confidence: 99%
“…Equally, hOMSCs have been successfully differentiated into osteoprogenitors and applied to close calvaria defects (Lopez-Letayf et al 2022). Mouse OMSCs were successfully used in treating of wounds in a diabetic mouse model (Kuperman et al 2020). Although molecular basis of all these observed therapeutic phenomena remains elusive, some articles suggested that at least a part of their beneficial effects was achieved over secretion of GFAP, VEGF and BDNF (Ganz et al 2014a, b).…”
Section: Introductionmentioning
confidence: 99%